Infusion therapy for chronic liver diseases - I. A. Kurkina; M. V. Mayevskaya; I. N. Tikhonov; V. N. Zozulya; V. I. Leschenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. To present modern options of comprehensive infusion therapy at various liver diseases, indications and contraindications for application of basic blood substitute groups, and pathogenically justified approaches for their use. Summary. Chronic and acute liver diseases are associated to end the genius intoxication, electrolyte disorders, shift of acid-base state, tissue and cellular hypoxia. Infusion therapy with application of modern plasma substitute solutions provide increase in treatment efficacy for this group of patients. Application of basic group infusion solutions along with complex anti-hypoxia agents helps to correct water and electrolyte imbalance as well as disorders of acid-base state, carry out body detoxication, normalize blood pressure, treat edema and ascites syndrome, protein-energy malnutrition, prevent renal value and other complications in liver cirrhosis patients. Comprehensive treatment of liver diseases includes application of modern infusion agents (anti-hypoxia/anti-oxidation) containing pharmacologically active metabolic substances that include succinate-containing drugs developed on the basis of succinic acid and its salts. Succinic acid is presumed to act as the paracrine agent produced by damage hepatocytes (e.g. at ischemia), affecting pericytes (Ito's cell) in the liver through SUCNR1receptors. It results activation of pericytes providing synthesis of extracellular matrix components that are involved in metabolism and regeneration of liver parenchyma cells. Conclusion. Addition of succinic acid-based medications to infusion therapy program for chronic liver diseases provides alleviation of basic clinical syndromes (intoxication, asthenic and autonomous nervous disorders, dyspeptic, cholestatic), and at patients with hepatocellular failure improvement of protein-synthetic liver function.